New Alternately Colored FRET Sensors for Simultaneous Monitoring of Zn(2+) in Multiple Cellular Locations - Miranda, Jose G. (Public Library of Science, 2012)
Genetically encoded sensors based on fluorescence resonance energy transfer (FRET) are powerful tools for reporting on ions, molecules and biochemical reactions in living cells. Here we describe the development of new sensors for Zn(2+)based on alternate FRET-pairs that do not involve the traditional CFP and YFP. Zn(2+) is an essential micronutrient and plays fundamental roles in cell biology. Consequently there is a pressing need for robust sensors to monitor Zn(2+) levels and dynamics in cells with high spatial and temporal resolution. Here we develop a suite of sensors using alternate FRET pairs, including tSapphire/TagRFP, tSapphire/mKO, Clover/mRuby2, mOrange2/mCherry, and mOrange2/mKATE. These sensors were targeted to both the nucleus and cytosol and characterized and validated in living cells. Sensors based on the new FRET pair Clover/mRuby2 displayed a higher dynamic range and better signal-to-noise ratio than the remaining sensors tested and were optimal for monitoring changes in cytosolic and nuclear Zn(2+). Using a green-red sensor targeted to the nucleus and cyan-yellow sensor targeted to either the ER, Golgi, or mitochondria, we were able to monitor Zn(2+) uptake simultaneously in two compartments, revealing that nuclear Zn(2+) rises quickly, whereas the ER, Golgi, and mitochondria all sequester Zn(2+) more slowly and with a delay of 600–700 sec. Lastly, these studies provide the first glimpse of nuclear Zn(2+) and reveal that nuclear Zn(2+) is buffered at a higher level than cytosolic Zn(2+).